Blood eosinophilia: A poor prognostic factor for primary cutaneous T cell lymphomas? A cohort of 72 cases - Kelati Awatef; Meziane Mariame; Mernissi Fatima Zahra (Our Dermatology Online, 2016)
Introduction: Blood eosinophilia (BE) is described as a poor prognosis marker for some T cell malignancies. Objective: to detect the presence and the prognostic significance of BE in patients with cutaneous T cell lymphoma (CTL). Methods: This was a retro prospective study of 72 patients with CTL. Patients with other factors that may increase BE were excluded. Results: We had 14 cases of BE, 10 cases were in the erythrodermic stage of the disease and 6 in the tumoral stage and we had 4 cases of death. The BE was associated with deterioration of the general condition (p=0.001); depilation of the body (p=0.04), erythroderma (p=0.008), scalp and nails involvement (p=0.000), high rate of lactate Dehydrogenase (LDH) (p=0.000) and beta 2 microglobulin (B2M), (p=0.000), the histological type of Mycosis fungoides (MF) with positive Immunohistochemistry for CD4 (p=0.014) and CD3(0.05). Conclusions: BE was significantly related to MF, to advanced stages of the disease, to pejorative clinical signs and to elevated rate of LDH and B2M which are poor prognostic factors of MF with four cases of death, which prove that BE is also a poor Prognostic factor of MF.